Head-impact mechanisms in men's and women's collegiate ice hockey - Wilcox, B. J.; Machan, J. T.; Beckwith, J. G.; Greenwald, R. M.; Burmeister, E.; Crisco, J. J. (Journal of Athletic Training, 2015)
Context: Concussion injury rates in men's and women's ice hockey are reported to be among the highest of all collegiate sports. Quantification of the frequency of head impacts and the magnitude of head acceleration as a function of the different impact mechanisms (eg, head contact with the ice) that occur in ice hockey could provide a better understanding of this high injury rate.